Analisis Pengaruh Strategi Pemasaran Dan Orientasi Wirausaha Terhadap Kinerja Pemasaran Yang Dimoderasi Oleh Lingkungan Persaingan (Studi pada Pengembang Real Estate di Sulawesi Utara) - Kaligis, Dirk (JURNAL RISET BISNIS DAN MANAJEMEN, 2015)
The purpose of this research is to analyzing the influence of marketing strategy and entrepreneur orientation to the marketing performance and the influence of marketing strategy to the marketing performance with the competition environment as moderator variable to the company of real estate developer in North Sulawesi. The population of this research is the 85 developers in North Sulawesi with the sampling that been used is saturated sampling. The analysis technique that been used is Moderator Regression Analysis. From the result of analysis showed that there is a significant influence between Marketing Strategy and Entrepreneur Orientation to the marketing performance while the competition environment not as the moderating variable that influence Marketing Strategy with marketing performance at the Real Estate Developer company in North Sulawesi Keywords: Marketing Strategy, Entrepreneur Orientation, Competition Environment, Marketing Performance